2004
DOI: 10.1038/sj.embor.7400209
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic movement of actin‐like proteins within bacterial cells

Abstract: Actin proteins are present in pro-and eukaryotes, and have been shown to perform motor-like functions in eukaryotic cells in a variety of processes. Bacterial actin homologues are essential for cell viability and have been implicated in the formation of rod cell shape, as well as in segregation of plasmids and whole chromosomes. We have generated functional green fluorescent protein fusions of all three Bacillus subtilis actin-like proteins (MreB, Mbl and MreBH), and show that all three proteins form helical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 25 publications
6
90
0
Order By: Relevance
“…Indeed, our recent results show that GFPMreB and GFP-Mbl filaments rapidly move along helical tracks around the whole cell diameter within about a minute, corresponding to a speed of 0.1 mm/s. (24) Given such dynamics, it is clear that bacterial actins could do more than just providing a helical cytoskeletal element: MreB or Mbl could in fact constitute an intracellular motor that might push molecules through the cell. Movement of Mbl could direct translocation of cell wall precursors and/or membrane proteins.…”
Section: Motor Functions Of Actin In Eukaryotic Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our recent results show that GFPMreB and GFP-Mbl filaments rapidly move along helical tracks around the whole cell diameter within about a minute, corresponding to a speed of 0.1 mm/s. (24) Given such dynamics, it is clear that bacterial actins could do more than just providing a helical cytoskeletal element: MreB or Mbl could in fact constitute an intracellular motor that might push molecules through the cell. Movement of Mbl could direct translocation of cell wall precursors and/or membrane proteins.…”
Section: Motor Functions Of Actin In Eukaryotic Cellsmentioning
confidence: 99%
“…Mbl filaments extend through the whole cell from pole to pole and have a longer lead (axial advance during one complete revolution of the helix) than MreB helices, while MreB filaments are usually absent from the cell poles. (16,24) Thus, the longer Mbl cables could dictate the cell's axis, while the more-central MreB filaments might control the width of the cell. How this control of rod cell shape works on molecular terms is still unknown.…”
Section: Motor Functions Of Actin In Eukaryotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, this movement was proposed to be caused by treadmilling of the MreB filaments (Soufo and Graumann, 2004; Kim et al, 2006). A revised hypothesis posited that the movement of the elongasome depends on PG synthesis, either by insertion of new glycan strands of PG by a bifunctional PBP in a pushing movement or by pulling of hydrolases degrading old PG strands (Errington, 2015).…”
Section: Generation Of Cell Shapementioning
confidence: 99%
“…These proteins change their pattern of localisation according to the cell cycle stage (Carballido-Lopez & Errington 2003, Figge et al 2004). Bundles of filaments move continuously and in parallel along helical tracks (Defeu-Soufo & Graumann 2004). It has also been suggested that these proteins are involved in the organisation of the cell wall, leading to the cells acquiring their typical rod-like shape (Daniel & Errington 2003).…”
Section: Tubulin-like Homologues -mentioning
confidence: 99%